THE PECULIARITIES OF HEGEL'S ETHICS - Rūta Marija Marija Vabalaitė (Problemos)
The article deals with four actual aspects of Hegelian philosophy of morals and education. It is argued that his propositions are significant for the program of the present moral education. The first peculiarity consists in the statements, that present the matter for an analysis of the principles of morals, that are simultaneous but taken one with another are not consistent with. The other peculiarity is a topic of an activity, of bringing the issues nearer to the real life, of the conscious motivation of the actions. That argument is of particular importance to a criticism of the apathy and weakness of the modern youth. The third aspect consists in the notion of the means of moral education. Hegel speaks ironically of unfounded and futile moralising, of the criticism of present morals from the point of view of proper one, that is invented but does not exist. The fourth peculiarity, that is closely tied to the third, is Hegelian certitude in the nature of the matter of training. He points to the priority of firm discipline of thinking and to the priority of the classical education. That statements give us an opportunity to think of substantiated evaluation of the limitless tolerance that exists in our culture. The contemporary notion of subject enables us to assert that in spite of the totalitarian features of Hegelian philosophical system, his theory of morals is valuable for youth's education.